The organization of serotonergic fibers in the Pacific angelshark brain: neuroanatomical and supercomputing analyses - Janušonis, Skirmantas; Metzler, Ralf; Vojta, Thomas (Frontiers in Neuroscience, 2025)
Serotonergic axons (fibers) are a universal feature of all vertebrate brains. They form meshworks, typically quantified with regional density measurements, and appear to support neuroplasticity. The self-organization of this system remains poorly understood, partly because of the strong stochasticity of individual fiber trajectories. In an extension to our previous analyses of the mouse brain, serotonergic fibers were investigated in the brain of the Pacific angelshark (Squatina californica), a representative of a unique (ray-like) lineage of the squalomorph sharks. First, the fundamental cytoarchitecture of the angelshark brain was examined, including the expression of ionized calcium-binding adapter molecule 1 (Iba1, AIF-1) and the mesencephalic trigeminal nucleus. Second, serotonergic fibers were visualized with immunohistochemistry, which showed that fibers in the forebrain have the tendency to move toward the dorsal pallium and also accumulate at higher densities at pial borders. Third, a population of serotonergic fibers was modeled inside a digital model of the angelshark brain by using a supercomputing simulation. The simulated fibers were defined as sample paths of reflected fractional Brownian motion (FBM), a continuous-time stochastic process. The regional densities generated by these simulated fibers reproduced key features of the biological serotonergic fiber densities in the telencephalon, a brain division with a considerable physical uniformity and no major “obstacles” (dense axon tracts). These results demonstrate that the paths of serotonergic fibers may be inherently stochastic, and that a large population of such paths can give rise to a consistent, non-uniform, and biologically-realistic fiber density distribution. Local densities may be induced by the constraints of the three-dimensional geometry of the brain, with no axon guidance cues. However, they can be further refined by anisotropies that constrain fiber movement (e.g., major axon tracts, active self-avoidance, chemical gradients). In the angelshark forebrain, such constraints may be reduced to an attractive effect of the dorsal pallium, suggesting that anatomically complex distributions of fiber densities can emerge from the interplay of a small set of stochastic and deterministic processes.